A comparative analysis of height trend and nutrition among 1983 to 2005 birth cohort of Ilorin metropolis, Kwara State, Nigeria - Ade Stephen Alabi; Peace Eyitayo Olagunju; Adeola Alabi; Joshua Abidemi Owa; Yetunde Elizabeth Owa; Abosede Mary Ayoola; Dare Ezekiel Babatunde; Oluwatoyin Ezekiel Olasehinde; Titilayo Temitope Adeoye (Anthropological Review)
Over the course of the years, numerous studies have been conducted to assess the trends in height across different generations and regions. This study seeks to add to the current data on secular height trend, by analyzing the trend in height, gender specific differences in height trend and relationship between socionutritional factors and increase in height trend among 1983–2005 birth cohort in the Ilorin metropolis. A total of 414 study participants aged 18–40 years (207 males and 207 females). Their height was obtained using the Tape stadiometer, information about dietary history (nutritional factors) that may affect height were gotten via the use of Questionnaires. Data were analyzed using the Statistical Package for Social Sciences (SPSS) Version 27.0 and results were computed using Pearson’s Chi-square analysis and ANOVA. P-values less than 0.05 were considered significant. Height was found to have positively increased among the 1983 to 2005 birth cohorts of Ilorin metropolis with the most significant increase being observed in the Males. This study also revealed a positive correlation between Diary and Carbohydrate consumption and increase in height, especially among males. No significant increase in height was found among females of the birth cohorts and no Association was found between the considered nutritional factors and female height.